2021
DOI: 10.3390/jmmp5030085
|View full text |Cite
|
Sign up to set email alerts
|

In-Line Height Measurement Technique for Directed Energy Deposition Processes

Abstract: Directed energy deposition (DED) is a family of additive manufacturing technologies. With these processes, metal parts are built layer by layer, introducing dynamics that propagate in time and layer-domains, which implies additional complexity and consequently, the resulting part quality is hard to predict. Control of the deposit layer thickness and height is a critical issue since it impacts on geometrical accuracy, process stability, and the overall quality of the product. Therefore, online feedback height c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Machine-vision sensing is a cost-effective and reliable method for obtaining multiple information through image processing, as opposed to expensive IR cameras [193,194]. It has been reported that results obtained from digital cameras only deviate by a mere 5% from the precise results obtained through an optical 3D scanner [193], making it a cost-effective options for layer height control [195][196][197]. Ultimately, the advantages of using machinevision sensing outweigh its alternative, laser-based scanning techniques, with the later further discussed in the following section.…”
Section: Vision-based Signalsmentioning
confidence: 99%
“…Machine-vision sensing is a cost-effective and reliable method for obtaining multiple information through image processing, as opposed to expensive IR cameras [193,194]. It has been reported that results obtained from digital cameras only deviate by a mere 5% from the precise results obtained through an optical 3D scanner [193], making it a cost-effective options for layer height control [195][196][197]. Ultimately, the advantages of using machinevision sensing outweigh its alternative, laser-based scanning techniques, with the later further discussed in the following section.…”
Section: Vision-based Signalsmentioning
confidence: 99%
“…In this study, the focus is to monitor the geometrical accuracy of the build parts; to detect normal, under-and overdeposition. There are two monitoring approaches of obtaining geometrical process signatures [16,36]: laser scanning-based [37][38][39][40][41][42] and machine vision-based [43][44][45][46][47][48], each with their strengths and weaknesses. Laser scanning-based monitoring system has been used to obtain more precise depth information on fabricated parts, i.e.…”
Section: B Geometrical Sensingmentioning
confidence: 99%
“…Among the several outputs that need to be monitored and controlled to ensure the quality of the process/component, standoff distance and layer height are very important. In fact, a wrong standoff distance can lead to height deviations from the ideal building path [6].…”
Section: Introductionmentioning
confidence: 99%